2017
DOI: 10.1007/s10071-017-1078-6
|View full text |Cite
|
Sign up to set email alerts
|

Deceptive-like behaviour in dogs (Canis familiaris)

Abstract: Deception, the use of false signals to modify the behaviour of the receiver, occurs in low frequencies even in stable signalling systems. For example, it can be advantageous for subordinate individuals to deceive in competitive situations. We investigated in a three-way choice task whether dogs are able to mislead a human competitor, i.e. if they are capable of tactical deception. During training, dogs experienced the role of their owner, as always being cooperative, and two unfamiliar humans, one acting 'coop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
2
21
1
1
Order By: Relevance
“…This added component of reasoning about deceptive intentions of an unhelpful informant is known to be a much harder theory of mind task than the knowledge-based tasks that both dogs and children succeed at (Shafto et al 2012 ). Intriguingly, there is some suggestive evidence that dogs may succeed at reasoning about deception, which may aid them in our task (Heberlein et al 2017 ). Nonetheless, dogs were at a disadvantage in our task when compared to children as, unlike in the work in children, we were unable to give the dogs verbal information about the accuracy of the informants in advance or provide context about what is expected of them by verbally describing the choice task.…”
Section: Discussionmentioning
confidence: 88%
“…This added component of reasoning about deceptive intentions of an unhelpful informant is known to be a much harder theory of mind task than the knowledge-based tasks that both dogs and children succeed at (Shafto et al 2012 ). Intriguingly, there is some suggestive evidence that dogs may succeed at reasoning about deception, which may aid them in our task (Heberlein et al 2017 ). Nonetheless, dogs were at a disadvantage in our task when compared to children as, unlike in the work in children, we were unable to give the dogs verbal information about the accuracy of the informants in advance or provide context about what is expected of them by verbally describing the choice task.…”
Section: Discussionmentioning
confidence: 88%
“…With regard to deception, dogs can also learn to respond differently to humans who habitually deceive them about the location of food, compared with truthful humans (Petter, Musolino, Roberts, & Cole, 2009), though this is effectively an operant discrimination task rather than requiring any special social cognition. Dogs themselves may engage in deception in play (Mitchell & Thompson, 1993), and they can learn to lead a human who will not share food with them away from the food source (Heberlein, Manser, & Turner, 2017), though this result can again be interpreted as differential conditioning, without the necessity of possessing a theory of mind.…”
Section: The Comparative Projectmentioning
confidence: 99%
“…These results suggest that dogs could accomplish some form of social categorization in order to select potential cooperators to ask for their help, taking into account behavioral characteristics similar to their owner. Furthermore, Heberlein, Manser, and Turner (2017) found that dogs indicated the location of hidden food more often to a person who had cooperated with them compared with someone who had been competitive. This study was not an unsolvable task but rather one of showing-a kind of task in which the animal watches food being hidden while a person is outside the room.…”
mentioning
confidence: 99%